Levels and criteria of readiness of future teachers to professional mobility (Pedagogy of Higher and Secondary Education, 2014)
Golovnya N. M. Levels and criteria of readiness of future teachers to professional mobility.This paper examines current approaches to the definition of "readiness" of native scientists and researchers. The author has determined the nature of future teachers` readiness to professional mobility. Basic stages of the formation of readiness to professional mobility, its criteria and levels of the development are defined.
Keywords: readiness; professional readiness; professional mobility